Moving on - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Pastoralism in the new millennium FAO Animal Production and Health Papers, 2001. 104 pp. ISBN 9251046735 US$14 Euro 13.60